Educational Game Introducing Cells in Animals and Plants Based on Android Using the Linear Congruential Generator Algorithm - Ina, Anggri Hada; Lede, Pingky Alfa Ray Leo; Mira, Trisari Dewi Novyanti B (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
In the world of education, science lessons have been taught since elementary school. However, material related to the introduction of animal and plant cells is only given at the junior high school level. State Junior High School 2 Kanatang, East Sumba is one of the secondary schools that provides introductory material to animal and plant cells for class VIII students. In teaching and learning activities, the delivery of material by teachers still uses limited teaching materials, which results in students not understanding the material related to the introduction of animal cells and plant cells. This is proven based on data on student scores for learning material on animal cells and plant cells. Student scores are still below average. flat. For this reason, an educational game about the introduction of cells in animals and plants was created to help students learn science. The method used in this research is the Multimedia Development Life Cycle (MDLC) method. In making the application, the Linear Congruential Generator algorithm was applied to randomize the practice questions in the educational game application for introducing cells in animals and plants. The aim of this research is to produce an educational game for recognizing cells in animals and plants which is able to improve students' ability to remember the cells in animals and plants at SMP N 2 Kanatang, East Sumba. The tools used to build this application are Unity.